Staphylococcal driveline infections are the predominant type of left ventricular assist device associated infections in Singapore. Issue 6 (3rd June 2019) - Teh, Yii Ean; Lim, Choon Pin; Teo, Louis Loon Yee; Soon, Jia Lin; Chao, Victor Tar Toong; Neo, Chia Lee; Tan, Joycelyn Li Li; Kerk, Ka Lee; Sim, David Kheng Leng; Tan, Teing Ee; Tan, Ban Hock; Cumaraswamy, Sivathasan; et al.
Abstract: Background : Left ventricular assist device (LVAD) associated infections (LVADIs) have substantial morbidity and mortality. We aim to describe the incidence and epidemiology of LVADIs in an Asian cohort. This is currently not well studied. Methods : We conducted a retrospective review of 52 patients who underwent LVAD implantation from 1 May 2009–31 December 2014 in National Heart Centre Singapore. LVADIs were defined based on definitions proposed by the International Society for Heart and Lung Transplantation. Results : There were 39 males and 13 females. Seventy-three percent had Heartmate II LVAD implant while 27% received Heartware HVAD. Eighty-one percent were implanted as bridge to heart transplantation, 19% as destination therapy. Forty-five episodes of LVADIs occurred in 25 patients. Overall LVADI incidence was 47.5 cases per 100 patient-years. Driveline infections (58%) were the commonest type of LVADI. The commonest causative organisms were coagulase-negative staphylococci (33%), Staphylococcus aureus (31%) and Corynebacterium species (19%). Twelve percent of patients with LVADI required surgical debridement and one patient required pump exchange due to pump pocket infection. All-cause mortality was 13%. Conclusions : The findings of our study add to the understanding and epidemiology of LVADIs, particularly in the Asian setting. This can contribute to the development of evidence based strategies to prevent and manage LVADIs.